ANFIS Control for Solar PV fed Modular Multilevel Inverter for Marine Water Pumping Applications - Rubi, V.Shalini; Kiranmayi, R.; Nagabhushanam, Sri K.; Swathi, N. (International Journal of Membrane Science and Technology, 2023)
In this paper, we show our work developing and implementing a Modular Multilevel Inverter (MMI) for intelligent Induction Motor (IM) drive control. Pumping water from the sea is the primary focus of these methods. It has been suggested that an eleven-stage inverter could be used to regulate the speed of a photovoltaic solar-powered IM drive. It is estimated that pumps account for roughly half of a ship's total energy consumption. Therefore, the purpose of this study is to investigate and assess the proposed control design for an induction motor (IM) drive and MMI-based marine water pumping system. The primary motivation behind this design was to reduce the complexity of the controller. Controllers based on Proportional-Integral (PI), Fuzzy Logic (FL), and Adaptive Network-based Fuzzy Interference System (ANFIS) are tested alongside the inverter to see how well they improve performance. The Total Harmonic Distortion (THD) of inverters, controller settling times, and peak overshoot have all been compared to identify the most robust option. In order to establish which of these elements is superior, this comparison was performed. The suggested control scheme's novel feature is the design and integration of a marine-specific MMI, IM drive, and intelligent controller for use in marine water pumping applications.